Improving Students’ Reading Skill through Webtoon Application: A Classroom Action Research at SMP Nurul Hasaniah Percut Sei Tuan - Dwi Suci Amaniarsih; Berlin Sibarani (EXCELLENCE: Journal of English and English Education, 2025)
This study aims to improve the reading comprehension skills of seventh-grade students at SMP Nurul Hasaniah, Percut Sei Tuan by using the Webtoon application as a learning medium. The study employed Classroom Action Research (CAR) following the Kemmis and McTaggart model, which consists of planning, acting, observing, and reflecting stages across two cycles. The research instruments included reading comprehension tests, observation sheets, field notes, documentation, and brief interviews. The findings revealed a significant improvement in students’ reading comprehension. The average score increased from 56.8 in the pre-cycle to 71.2 in Cycle I, and to 83.4 in Cycle II. The percentage of students achieving the Minimum Mastery Criterion (≥ 70) rose from 24% to 68% in Cycle I, and reached 92% in Cycle II. The use of Webtoon also enhanced students’ motivation, engagement, and enthusiasm during reading activities. Its multimodal features—visuals, dialogues, and narrative structure—effectively supported students’ understanding of context, vocabulary, and storyline. Therefore, Webtoon can be considered an effective alternative digital learning medium for improving junior high school students’ reading comprehension.